Pancasila dan Piagam Madinah: Konvergensi Nilai-Nilai dalam Prespektif Ideologi Negara - Dzikrullah Faza, M.; Ghulam, Hafiz; Saidou, Ouedraogo (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
As a country with the largest number of Muslim populations in the world, the ideology of Pancasila is often contradicted, as if it is incompatible with the identity of an Islamic state. In fact, the debate about the form and sovereignty of the Indonesian state is final and discussed strictly by the hero of the proclamation of independence. This article is classified as literature research with a qualitative approach. The methodology used is content analysis and a comparative study between the Pancasila ideology and the Medina Charter. The results of the study concluded two things: first, the Prophet did not specifically formulate the formal form of an Islamic state, but what the Prophet emphasized was the importance of a state that adheres to Islamic values. Second, although Indonesia is not an Islamic country, the ideology of Pancasila does not contradict, let alone ignore, the essence of Islam and the existence of adherents to it.